2014
DOI: 10.4330/wjc.v6.i9.1030
|View full text |Cite
|
Sign up to set email alerts
|

Does manual thrombus aspiration help optimize stent implantation in ST-segment elevation myocardial infarction?

Abstract: AIM:To evaluate the impact of thrombus aspiration (TA) on procedural outcomes in a real-world ST-segment elevation myocardial infarction (STEMI) registry. METHODS:From May 2006 to August 2008, 542 consecutive STEMI patients referred for primary or rescue percutaneous coronary intervention were enrolled and the angiographic results and stent implantation characteristics were compared according to the performance of manual TA. RESULTS:A total of 456 patients were analyzable and categorized in TA group (156 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Also, the mean length of the stented segments was significantly lower in the thrombectomy group than in the conventional group (22.5 ± 13 vs 28.5 ± 15 mm, respectively, p = 0.001). Along the same line, Rodriguez et al, (2014) [28] reported a mean length of stented segments of (24.1 ± 11.8 vs 26.9 ± 15.7 mm, p = 0.03). In the current study, the thrombectomy group required fewer stents (1 ± 0.5 vs 1.2 ± 0.6, p = 0.001).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Also, the mean length of the stented segments was significantly lower in the thrombectomy group than in the conventional group (22.5 ± 13 vs 28.5 ± 15 mm, respectively, p = 0.001). Along the same line, Rodriguez et al, (2014) [28] reported a mean length of stented segments of (24.1 ± 11.8 vs 26.9 ± 15.7 mm, p = 0.03). In the current study, the thrombectomy group required fewer stents (1 ± 0.5 vs 1.2 ± 0.6, p = 0.001).…”
Section: Discussionmentioning
confidence: 75%
“…In our study, direct stenting was more frequent in the thrombectomy group than the conventional group (38% vs 20%, p = 0.001). Rodriguez et al, (2014) [28] reported direct stenting rates of (58% vs 45% for the thrombectomy group vs the conventional group, p = 0.009).…”
Section: Discussionmentioning
confidence: 99%